Public Debt And Its Impact On The Net Public Budget In Iraq For The Period (2004-2023): An Econometric Study Using The Ardl Cointegration Model - Marwa Allawi Naji (Research Parks Publishers, 2026)
The research aims to analyze and measure the relationship between the impact of public debt and the net public budget in Iraq for the period (2004-2023), as they are economic variables of great importance and influence in the Iraqi economy, On this basis, the variables under study were analyzed and measured using the standard ARDL model for distributed slowdown, relying on the stability results, which showed that the variables (public debt and net budget) are stable at the level and first difference , The results of this model showed that there is a long-term cointegration between the public debt and the net budget, as well as the absence of an autocorrelation problem. Accordingly, the null hypothesis was accepted and the alternative hypothesis was rejected because the probability values were greater than (0.05), and then a set of conclusions and recommendations were reached.